Evaluation of Heart Rate, Work Rate and O2 Uptake Relationships During Constant Load Exercise Test Work Load at the Anaerobic Threshold in Healthy Male - Ugras, Seda; Ozceli̇k, Oguz (Dicle Medical Journal/Dicle Tip Dergisi, 2020)
Objectives: During an incremental exercise test, increased metabolic demands of exercising muscle should be compensated with increased O2 uptake and heart rate until to their maximal levels. Anaerobic threshold (AT) describes the point of metabolic transition from aerobic to anaerobic metabolism and reflect moderate exercise intensity. The aim of this study was to evaluate O2 uptake to heart beat ratio (O2 pulse) and heat rate to work rate ratio (HR/WR) in response to constant load exercise at work load corresponded to AT.
Method: Twelve healthy young male subjects initially performed an incremental exercise test (15 W/min) until exhaustion. Then, each subject performed a 30 min of constant load exercise test that work load at their AT on separate days. Pulmonary gas exchange parameters were measured breath-by breath using a metabolic gas analyser. Cardiac parameters were followed continuously beat-by beat using a 12 lead ECG. AT estimated non-invasively using V-slope method.
Results: The heart rate for each watt of work production (HR/WR) was ranged between 0.97 beat/min/W to 1.76 beat/min/W and averaged 1.25±0.2 beat/min/W. The O2 pulse was ranged between 10.56 mL/min/beat to 16.15 mL/min/beat and averaged 13.38±1.5 mL/min/beat at the end of the test. A negative statistically significant correlation (R = - 0.90316, p
Keywords: Health Care Administration; Exercise; Anaerobic threshold; O2 pulse; fitness status; heart rate to work rate ratio; Sağlık Kurumları Yönetimi